2015
DOI: 10.2147/dddt.s75980
|View full text |Cite
|
Sign up to set email alerts
|

A fixed-dose combination tablet of gemigliptin and metformin sustained release has comparable pharmacodynamic, pharmacokinetic, and tolerability profiles to separate tablets in healthy subjects

Abstract: BackgroundIn type 2 diabetes mellitus, fixed-dose combination (FDC) can provide the complementary benefits of correction of multiple pathophysiologic defects such as dysfunctions in glycemic or metabolic control while improving compliance compared with separate tablets taken together. The objective of the study reported here was to compare the pharmacodynamic (PD), pharmacokinetic (PK), and tolerability profiles of gemigliptin and extended-release metformin (metformin XR) between FDC and separate tablets.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Because the degree of inhibition of DPP-4 activity is a direct PD biomarker of DPP-4 inhibitors, 14 , 22 , 23 this study measured the plasma DPP-4 activity to evaluate the PDs of gemigliptin in the two formulations, and similar values for AUEC last and I max were observed regardless of the formulation. Recently, several studies showed that the degree of inhibition of DPP-4 activity after administration of DPP-4 inhibitors was comparable in normoglycemic and diabetic subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Because the degree of inhibition of DPP-4 activity is a direct PD biomarker of DPP-4 inhibitors, 14 , 22 , 23 this study measured the plasma DPP-4 activity to evaluate the PDs of gemigliptin in the two formulations, and similar values for AUEC last and I max were observed regardless of the formulation. Recently, several studies showed that the degree of inhibition of DPP-4 activity after administration of DPP-4 inhibitors was comparable in normoglycemic and diabetic subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, these results are consistent with a similarly designed study comparing two tablets of the FDC (gemigliptin/metformin SR 25/500 mg), collectively, 50 mg and 1,000 mg, and the separate tablets. 16 The reference tablets used in this study were the same as those used in the pivotal safety and efficacy studies for each agent, thus providing a direct link with the FDC tablet. Additionally, the peak and total exposures of LC15-0636 (metabolite of gemigliptin) were similar in both the FDC tablet and the individual tablets, further supporting the interchangeability of the FDC tablet and the individual tablets (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that the pharmacokinetics, pharmacodynamics, and tolerability profile of gemigliptin and metformin were comparable in healthy subjects who were administered a FDC (gemigliptin/metformin SR 25 mg/500 mg) and co-administered two individual tablets. 16 The objective of this study was to establish pharmacokinetic equivalence between the higher dose strength FDC tablet (gemigliptin/metformin SR 50/1,000 mg) and the corresponding co-administered doses of gemigliptin and metformin as individual tablets in healthy male volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…We observed two reasons for the absence of validation data in the articles: the study was performed before the guidelines had been published [53][54][55][56][57][58][59][60][61][62][63][64][65][66]; and the study focus was on method development and validation was not addressed [67][68][69][70][71][72]. Other reasons for excluding articles were: non-simultaneous method [74][75][76][77], inappropriate sample preparation [78,79], literature review [80], animal plasma sample [81], language in non-Roman characters [82][83][84], validation of only one analyte [85,86], and pharmacokinetic studies (PK) that used a previously developed and validated method [87][88][89][90][91][92][93][94][95][96][97].…”
Section: Systematic Literature Searchmentioning
confidence: 99%